Burma dealing with the devil - Journeyman Pictures ([S.l.] : Journeyman Pictures, 2004)
Peace signing between the Burma military Junta and the Karen ethnic which would leave Aung san Suu Kyi increasingly isolated
Keywords: Burma -- Politics and government